Remediation using SSCS model for reducing misconceptions about work and energy - M Ahsanul Taqwim; Widha Sunarno; Murni Ramli (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2022)
Misconceptions are discrepancies between students' understanding of concepts and concepts defined by experts. Misconceptions are indicated as latent dangers in the learning process. One of the topics in science that has a high level of misconception among students is the concept of work and energy. The SSCS model is an approach put forward as an effective way to train students' conceptual understanding. This research aims to determine whether the misconceptions about the work and energy of grade 7 students will be reduced by applying the SSCS model (Search, Solve, Create, and Share) as a remediation approach. The experimental design was applied using a one-group pretest-posttest design. The research sample comprised 32 students (15 boys and 17 girls). Profiling of students' misconceptions before and after the action was measured using 14 two-level multiple-choice questions. There are four types of misconceptions based on initial measurements. The results show an average pretest score of 44.07 and an average posttest of 63.60. It can be concluded that the SSCS model significantly reduces student misconceptions. Further research on the types of errors present in mapping student profiles is recommended.